Auto-landing algorithm for quadrotor UAV using super-twisting second-order sliding mode control in the presence of external disturbances - Danesh, Mohammad; Jalalaei, Amirhossein; Derakhshan, Reza Ebrahimpour (International journal of dynamics and control, 2023)
In this paper, first, quadrotor dynamical equations are derived, and then, an auto-landing algorithm is designed to land a quadrotor UAV on a specified location. A double-loop control structure with inner and outer loops is presented to stabilize the system in the presence of external time-varying disturbances and wind gusts. In the inner loop, a controller is utilized based on the super-twisting second-order sliding mode control (ST-SOSMC) approach to control the rotational dynamics. The outer loop comprises proportional-derivative (PD) controllers to stabilize the translational dynamics of the system. In the designed auto-landing algorithm, an interpolation-based method is adopted to generate desired trajectories which then the proposed PD-(ST-SOSMC) scheme is used to perform the trajectory tracking task. Compared to the classical first-order SMC, the ST-SOSMC can solve the chattering problem besides providing robustness against modeling errors, uncertainties, and different disturbances. Simulation results show the feasibility and effectiveness of the proposed auto-landing algorithm and control scheme in desired path following and disturbance rejection.